Manifesting America the imperial construction of U.S. national space - Rifkin, Mark, 1974- (Oxford University Press, 2009)
In this work, Mark Rifkin explores how writings by Native Americans and former Mexicans challenge the legal narratives that normalize their absorption into US national space.